Nonstandard inner products and preconditioned iterative methods - Pestana, J (2011)
By considering Krylov subspace methods in nonstandard inner products, we develop in this thesis new methods for solving large sparse linear systems and examine the effectiveness of existing preconditioners. We focus on saddle point systems and systems with a nonsymmetric, diagonalizable coefficient matrix. For symmetric saddle point systems, we present a preconditioner that renders the preconditioned saddle point matrix nonsymmetric but self-adjoint with respect to an inner product and for which scaling is not required to apply a short-term recurrence method. The robustness and effectiveness of this preconditioner, when applied to a number of test problems, is demonstrated. We additionally utilize combination preconditioning (Stoll and Wathen. SIAM J. Matrix Anal. Appl. 2008; 30:582-608) to develop three new combination preconditioners. One of these is formed from two preconditioners for which only a MINRES-type method can be applied, and yet a conjugate-gradient type method can be applied to the combination preconditioned system. Numerical experiments show that application of these preconditioners can result in faster convergence. When the coefficient matrix is diagonalizable, but potentially nonsymmetric, we present conditions under which the pseudospectra of a preconditioner and coefficient matrix are identical and characterize the pseudospectra when this condition is not exactly fulfilled. We show that when the preconditioner and coefficient matrix are self-adjoint with respect to nearby symmetric bilinear forms the convergence of a particular minimum residual method is bounded by a term that depends on the spectrum of the preconditioned coefficient matrix and a constant that is small when the symmetric bilinear forms are close. An iteration-dependent bound for GMRES in the Euclidean inner product is presented that shows precisely why a standard bound can be pessimistic. We observe that for certain problems known, effective preconditioners are either self-adjoint with respect to the same symmetric bilinear form as the coefficient matrix or one that is nearby.